2018
DOI: 10.21161/mjm.96316
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vibrio parahaemolyticus isolated from coastal water in Eastern Province of Saudi Arabia

Abstract: Aims: Vibrio parahaemolyticus is a marine and estuarine bacterium that has been documented as the causative agent of food-borne outbreak worldwide. The aim of this study was to confirm the identification of presumptive V. parahaemolyticus isolates to the species level by using PCR targeted to the outer membrane protein regulation operon gene (toxR) and to investigate antibiotic resistance, plasmid profile, and the main core virulence genes of thermostable direct hemolysin (tdh) and tdh-related hemolysin (trh).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…The ERIC-PCR clusters indicate that the isolates could have originated from the same clonal lineage of V. parahaemolyticus . These results agreed with our previous study ( Elhadi & Nishibuchi, 2018 ) and are consistent with Marshall et al (1999) , who reported that ERIC-PCR was a useful method for evaluating genetic and epidemiological relationships among V. parahaemolyticus . The results obtained in this study are very significant for public health in this coastal region and should prompt us to pay attention to the role of these tdh positive V. parahaemolyticus in local foodborne diseases.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The ERIC-PCR clusters indicate that the isolates could have originated from the same clonal lineage of V. parahaemolyticus . These results agreed with our previous study ( Elhadi & Nishibuchi, 2018 ) and are consistent with Marshall et al (1999) , who reported that ERIC-PCR was a useful method for evaluating genetic and epidemiological relationships among V. parahaemolyticus . The results obtained in this study are very significant for public health in this coastal region and should prompt us to pay attention to the role of these tdh positive V. parahaemolyticus in local foodborne diseases.…”
Section: Discussionsupporting
confidence: 93%
“…The highest percentage of tdh positivity was 17.5% from the total isolates detected among V. parahemolyticus isolated with IMB enrichment, while the lowest percentage of tdh positive isolates was (2.5%) detected in V. parahaemolyticus isolated without IMB enrichment ( Table 3 ). From our previous studies were conducted to investigate the presence of toxigenic V. parahaemolyticus in costal environment of the Eastern Province of Saudi Arabia, revealed none or less than 1% detection rate of isolates positive for virulence gene markers ( Elhadi & Nishibuchi, 2018 ; Ghenem & Elhadi, 2018 ). The detection of TDH positive strains of V. parahaemolyticus in the costal environment of the Eastern Province of Saudi Arabia is a pressing concern that has several impacts and requires instant attention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA extraction was done for all selected colonies on TCBS and CaV agar isolated with and without IMB as described elsewhere (Elhadi et al, 2018). Briefly, 1 ml of an overnight test culture in Luria Bertani (LB) broth was transferred into a 1.5 ml tube and centrifuged at 10,000 rpm for 2 min, and the supernatant was discarded.…”
Section: Dna Template Preparationmentioning
confidence: 99%